The development of prosociality: Evidence for a negative association between age and prosocial value orientation from a representative sample in Austria - Alexander Ehlert; Robert Böhm; Jürgen Fleiß; Heiko Rauhut; Robert Rybnicek; Fabian Winter (Games, 2021)
While the ontogeny of prosociality during infancy, childhood, and adolescence has received substantial attention over the last decades, little is known about how prosocial preferences develop beyond emerging adulthood. Recent evidence suggests that the previously observed positive association between age and prosocial preferences is less robust than assumed. This study reports results on the association between social preferences, age, gender, and education from an Austrian representative sample (N = 777, aged 16-94 years) in which incentivized social value orientations (SVO) were measured along with various other sociodemographic characteristics. The analyses confirm that men are less prosocial than women, however, mainly during emerging adulthood (16-25 years). At the same time, the decline of prosociality is stronger among women leading to a convergence of prosociality between men and women as they age. Overall, we find that a prosocial value orientation is negatively correlated with people's age. We suspect that the susceptibility of peoples' social preferences to the preferences of others in their social environment is a critical factor unifying these different observations in the development of prosociality. We hypothesize that the opposite associations between age and SVO observed in two previous studies using unincentivized measures of social preferences are explained in parts by an age-related change in social desirability, measurement inaccuracy (continuous vs. categorical), and cross-cultural differences promoting competitive preferences among emerging adults in Japan. Moreover, we find that political orientations towards right-wing populists are consistently associated with less prosocial preferences, while education seems to be positively associated with prosociality. Overall, our study highlights the importance of conducting representative studies using incentivized measurements across cultures.
Keywords: 330; age-related differences; human altruism; incentivized field experiments; ontogeny of prosociality; representative sample